2010
DOI: 10.1097/ta.0b013e3181e70f90
|View full text |Cite
|
Sign up to set email alerts
|

Quality in Trauma Care: Improving the Discharge Procedure of Patients by Means of Lean Six Sigma

Abstract: Our study shows that Lean Six Sigma is an effective method to reduce inappropriate hospital stay, thereby improving the quality and financial efficiency of trauma care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 17 publications
0
60
0
2
Order By: Relevance
“…Altogether these practices should decrease the time from injury to surgery and should minimize hospital LOS. [42][43][44] Patients with pelvis and acetabulum fractures and complications over their course of care had longer ICU and regular hospital stays, accounting for additional $14,829 in mean costs per patient. Other studies have also demonstrated greater treatment costs along with better margins in trauma patients who had complications.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether these practices should decrease the time from injury to surgery and should minimize hospital LOS. [42][43][44] Patients with pelvis and acetabulum fractures and complications over their course of care had longer ICU and regular hospital stays, accounting for additional $14,829 in mean costs per patient. Other studies have also demonstrated greater treatment costs along with better margins in trauma patients who had complications.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is this improvement in efficiency and throughput that is the goal of LOS reduction. 7 This efficiency is necessary in modern health care because of the increasing demand for trauma beds, seen with increased trauma admissions and a concurrent decrease in number of beds available for trauma patients. This efficiency must be gained without a loss in quality.…”
Section: Discussionmentioning
confidence: 99%
“…6 The manufacturing quality tools such as Lean management (LM) and Six Sigma (SS) are being implemented more frequently at hospitals around the world in an effort to raise patient and personnel satisfaction as well as improving healthcare quality on different settings, increasing efficiency and saving unnecessary costs. [7][8][9][10][11] In a systematic review of the literature, 177 articles on productivity tools used in health care have been published during the last decade. 12,13 These reports have shown that the implementation of process improvement tools positively impact OR efficiency without impairing the quality of patient care.…”
Section: Discussionmentioning
confidence: 99%